Larvicidal Property of the Acidified Chitosan from Marine Crab Shell Wastes against Aedes aegypti - Perez, Rosalle Moreno; Endaya, Rosar Jane Totong; Mohammad, Fharnieza Sabdula; Sepe, Melbert Cabañog (Asian Journal of Biological and Life Sciences, 2020)
Dengue outbreaks cause elevated death toll yearly leading to human health concerns, particularly in tropical areas. The basic way to reduce mosquito densities is targeting its larval stage through alternative control management. This study investigates the use of chitosan, extracted fromR. raninacrab shells obtained as common throwaways of seafood restaurants, as larvicide againstA. aegypti.Powderized crab shells undergo through deproteinization and demineralization to make chitin and further converted into chitosan by deacetylation. Batches of 30 third instar larvae were used for each treatment prior for larvicidal bioassay. Mortality was recorded after 24 and 48 hr exposure. Data were pooled from all replicates for analyses. Regression analysis of logprobit was determined to calculate the lethal concentration (LC50). Results revealed that acidified chitosan have increasing mortality rate ofA. aegyptilarvae as concentration increases. Among all treatments, 10000 ppm acidified chitosan possess the highest toxicity effect againstA. aegyptilarvae and as good and effective as the commercial larvicide. Acetic acid has no significant change in the mortality indicating that the larvicidal activity was due to the acidified chitosan. The LC50was estimated at 6654.181 and 4942.489 ppm after 24 and 48 hr, respectively. With longer exposure, repressed growth and disintegration of body tissues ofA. aegyptilarvae were observed. This may suggest that the acidified chitosan has a potential to disrupt metabolic responses and inhibit growth development. This study emphasizes the utilization of waste materials can be developed as good alternative larvicides that are environmentally safe and inexpensive.
Keywords: Aedes aegypti; Chitosan; Larvicidal; Lethal concentration; Mortality rate; Mosquitoes; Ranina ranina